De la desesperación de Sören Kierkegaard, a la angustia de Martin Heidegger - Falla Guirao, Miryam (2011)
Postmodernism has conducted to the man to questioning his existence and place notion in the  world. The excess of welfare and progress couldn't fulfill with all the “human” aspirations. It is related to a lack of creativity, dysfunction on interpersonal relationships, depression and existential anxiety. The anxiety in front of the inescapable death which is not sure when it will happen, leads the man to a system of internal annihilation and desperation. That is why hementions: “either Caesar or nothing”. Therefore, Martín Heidegger recognizes the “anxiety” in which succumbs the “being” facing death that is a “mystery”. The sense of the existence must be confronted without avoiding the fact of the deepest fears as anxiety, desperation or boredom.